The Impact on Inventory with the Implementation of RFID into SCOR based ERP Modules - Billy Gray; Erick Jones; Walter Mulflur; Christian Alvarez (International Journal of Supply Chain Management, 2013)
Many ERP systems on the market today follow some of the same guidelines based on the SCOR model. Through the various modules in each system, they implement the different aspects of the model in Plan, Source, Make, Deliver, and Return. Many of the activities in these systems are manual and prone to data entry mistakes forcing the system to be less reliable than it could be. RFID is a technology that has been used to reduce these errors and increase the speed at which the data is obtained and implemented in the system. It is hypothesized that by implementing RFID into specific components used in the modules in the ERP system that the technology will have an impact on the inventory value. The expected results will be that by implementing RFID technology, the inventory values will be reduced and prove to be beneficial.